2016
DOI: 10.1097/dss.0000000000000642
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Efficacy and Tolerability of Glycolic Acid, Salicylic Mandelic Acid, and Phytic Acid Combination Peels in Melasma

Abstract: It is concluded that GA (35%) and SM acid peels are both equally efficacious and a safe treatment modality for melasma in Indian skin, and are more effective than phytic acid peels. Salicylic-mandelic peels are better tolerated and more suitable for Indian skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 16 publications
1
59
1
5
Order By: Relevance
“…The large molecular weight of mandelic acid may produce a more uniform effect due to greater skin retention and slower penetration of the strateum corneum. It is also generally well tolerated by sensitive skin 18,20 and no patients in our study reported any degree of skin irritation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The large molecular weight of mandelic acid may produce a more uniform effect due to greater skin retention and slower penetration of the strateum corneum. It is also generally well tolerated by sensitive skin 18,20 and no patients in our study reported any degree of skin irritation.…”
Section: Discussionmentioning
confidence: 60%
“…Most literature suggests its use for the treatment of acne or hyperpigmentation. [18][19][20] It is of interest to note that the ancient Egyptians first used a form of a mandelic acid compound to improve the aging effects on facial skin, 3,600 years ago. 21 Our interest was to elucidate its possible effects on the physical properties of the skin.…”
mentioning
confidence: 99%
“…The scale consists of 10 questions pertaining to the quality of life and impact of the disease rated on a Likert scale. Other psychometric scales that can be used in those with melasma are the Dermatology Life Quality Index (DLQI) and the SKINDEX-16 [ 42 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alpha hydroxy acids (AHAs), including glycolic acid (GA) and citric acid, are naturally occurring organic acids commonly present in foods. GA has been established as a safe, nontoxic substance in fruits and participates in multiple bioactivities such as inducing antioxidant activity, increasing the effects of melasma treatment, and biosynthesizing ceramide [1,2]. GA was initially used to treat disorders of keratinization [3], and was used for increasing the production of dermal and epidermal glycosaminoglycans to prevent both dermal and epidermal atrophy resulting from longterm topical corticosteroid use [4].…”
Section: Introductionmentioning
confidence: 99%